2020
DOI: 10.1186/s12951-020-00725-z
|View full text |Cite
|
Sign up to set email alerts
|

Self-assembled bovine serum albumin nanoparticles as pesticide delivery vectors for controlling trunk-boring pests

Abstract: Background Trunk-boring pests (TBPs) are an important type of forest pest, TBPs not only feed on the branches and trunks of trees, but also spread quarantine diseases in forests. However, because the larvae of TBPs live inside the trunk and are well concealed, prevention and control are difficult. The lack of effective control methods leads to the death of many trees in forests. In this study, a novel nanopesticide featuring high bioactivity and slow-release properties was developed to control … Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
11
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
8
1

Relationship

2
7

Authors

Journals

citations
Cited by 17 publications
(12 citation statements)
references
References 50 publications
0
11
0
Order By: Relevance
“…In order to study the pesticide loading capacity of CuBTC, a saturated solution of AM/methanol was prepared, 20 mg CuBTC powder was dispersed in different volumes of AM solution, and stirred at 300 rpm for 48 h. After that, the supernatant was collected at 14,000 rpm for 20 min to measure the content of free AM using a UV spectrophotometer at a detection wavelength of 245 nm. The loading efficiency was calculated according to the following formula [ 36 ]. …”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…In order to study the pesticide loading capacity of CuBTC, a saturated solution of AM/methanol was prepared, 20 mg CuBTC powder was dispersed in different volumes of AM solution, and stirred at 300 rpm for 48 h. After that, the supernatant was collected at 14,000 rpm for 20 min to measure the content of free AM using a UV spectrophotometer at a detection wavelength of 245 nm. The loading efficiency was calculated according to the following formula [ 36 ]. …”
Section: Methodsmentioning
confidence: 99%
“…The contact toxicity and stomach toxicity of AM@CuBTC were determined by the pesticide membrane contact method and the feed mixing pesticide method [ 36 , 37 ]. Firstly, the dispersed AM@CuBTC solution was placed in a petri dish, and the filter paper was slowly spread into it to make it completely soaked, then the filter paper was turned upside down to the top, and the well-developed larva after starving for 24 h were placed on the filter paper to observe the pesticide intake of the larvae’s abdomen.…”
Section: Methodsmentioning
confidence: 99%
“…5B) remained basically unchanged at different temperatures, which indicated that AVM@CuBTC could be stable within a certain temperature range. As introduced in the previous article, the half-life of AVM was short, the characteristic structure of the conjugated double bond and the 16-membered ring macrolide structure made it easy to degrade under light [42]. Therefore, the retention of AVM after treatment was measured to clarify the protective effect of AVM@CuBTC (Fig.…”
Section: Stability Of Avm@cubtcmentioning
confidence: 99%
“…Additionally, hollow porous silica nanospheres (BHSNs) with a bowl-like structure were added to the model pesticide imidacloprid, which can aid to create the pesticide’s prolonged release through an adsorption and retention mechanism between the pesticide and the carrier [ 127 , 128 ]. Su et al created novel nano-pesticides with high biological activity and slow-release properties that can control the trunk borers by self-assembling the hydrophobic pesticide thicloline (THI) inside of the oleophobic feature of BSA [ 129 ]. According to studies, carbon nanomaterials (CNMs) can be employed as a vehicle for nanoscale sustained-release insecticides [ 130 ].…”
Section: Effect Of Nanomaterials (Nms) On Nutritional Quality Of Agri...mentioning
confidence: 99%